A Severity-Based Clinical Staging Model for the Psychosis Prodrome: Longitudinal Findings From the New York Recognition and Prevention Program - Carrión, Ricardo E. (Schizophr Bull, 2017)
Clinical staging improved the possibility of intervening during the psychosis prodrome to limit progression of illness. The current study aimed to validate a novel 4-stage severity-based model with a focus on clinical change over time and risk for conversion to psychosis. One hundred seventy-one individuals at clinical high risk (CHR) for psychosis were followed prospectively (3 ± 1.6 y) as part of the Recognition and Prevention (RAP) program and divided into 4 diagnostic stages according to absence/presence and severity of attenuated positive symptoms. Twenty-two percent of the combined sample recovered (no prodromal symptoms) by study outcome. The negative symptoms only subgroup had the highest symptom stability (70%), but the lowest conversion rate at 5.9%. The subgroup with more severe baseline attenuated positive symptom levels had a higher conversion rate (28%) and a more rapid onset when compared to the moderate attenuated positive symptom subgroup (11%). Finally, the Schizophrenia-Like Psychosis (SLP) subgroup showed low stability (3%), with 49% developing a specific psychotic disorder. The proposed stage model provides a more finely grained classification system than the standard diagnostic approach for prodromal individuals. All 4 stages are in need of early intervention because of low recovery rates. The negative symptom only stage is possibly a separate clinical syndrome, with an increased risk of functional disability. Both subgroups with attenuated positive symptoms are appropriate for studying the mechanisms of psychosis risk, however, individuals with more severe baseline positive symptoms appear better suited to clinical trials. Finally, the SLP category represents an intermediate outcome group appropriate for preventative intervention research but questionable for inclusion in prodromal studies of mechanisms.